Cooperative wideband spectrum sensing in suspicious cognitive radio network. Issue 2 (1st June 2013) - Srinu, Sesham; Sabat, Samrat Lagnajeet
Abstract : This study presents a cooperative wideband spectrum‐sensing technique based on the entropy of the received signal in the frequency domain. To enhance the efficiency of detection, multiple suspicious cognitive users are excluded from the network using generalised extreme studentised deviate test and sigma limit test. The performance of the proposed technique is compared with the energy detection technique under different channel environments. The simulation results demonstrate that the entropy detection method, with excluded suspicious users, has 9 dB improvement in performance compared to the energy detection technique in extremely low signal‐to‐noise ratio regime. This is a significant improvement for cognitive radio systems. The simulations were performed with false alarm probability and detection probability of 0.01 and 0.9, respectively. The hardware‐in‐the‐loop simulation of the proposed algorithm is further carried out in the Xilinx Virtex‐4 Field Programmable Gate Array.